The Effects of Perceived Stress and Attitudes Toward Menopause and Aging on Symptoms of Menopause - Nosek, Marcianna (2010)
As part of a longitudinal study of midlife women, the aim of this investigation was to describe the intensity of menopausal symptoms in relation to level of perceived stress in a woman’s life and her attitudes toward menopause and aging. Data were collected on 347 women between the ages of 40–50 in Northern California who began the study while pre-menopausal. Women self identified as African American, European American, or Mexican/Central American. Data collected over 3 time points in the first 12 months were used for this analysis. An investigator-developed tool for perception of specific types of stress was used. Attitudes toward menopause and aging were measured using the Attitudes Toward Menopause and Attitude Toward Aging Checklists. Attitudes toward aging and menopause, perceived stress, and income were related to intensity of symptoms. There was no ethnic group difference in perceived stress or attitude toward menopause. However, European and African Americans had a more positive attitude toward aging than Mexican/Central Americans. A lower income, higher perceived stress, a more negative attitude toward aging, and a more positive attitude toward menopause influenced menopausal symptom experience.